IMPLEMENTATION OF STUDENTS SOCIAL ATTITUDE IN THEMATIC LEARNING AT CLASS IVA OF ELEMENTARY SCHOOL - Micko Yulandri; Febrina Dafit (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2022)
Social attitude refers to the becoming of students' social attitudes in order to make them honest, disciplined, responsible, and caring for others. The research described in this article is to describe the students’ becoming of social attitudes and obstacles found by teachers in applying social attitudes in thematic learning. The method used is descriptive research with a qualitative approach. The research involved students and homeroom teachers at class IVA. The data collection method is carried out by observation, interviews, and documentation. The results indicate that the circumstances in the research field teachers and students have already embedded social attitudes in the teaching and learning processes. The social attitudes that appeared in this research are tolerance, self-confidence, and mutual cooperation. The implementation of social attitudes is seen when group discussion and learning interactions in the classroom. Yet, the implementation of these social attitudes has not been applied optimally. It is due to several existing inhibition factors like students’ low self-awareness, uncontrolled associations, and children’s inner behavior. However, teachers should be tried to adapt themselves to students through socialization such as in school, family, and society. Various attempts are given by teachers in order to make students instill their social attitudes like maximizing the application of teaching and learning methods, linking the material with social attitudes, and providing guidance to apply learning methods in groups.